Citrate‐Buffered Dialysis Solution (Citrasate) Allows Avoidance of Anticoagulation During Intermittent Hemodiafiltration—At the Cost of Decreased Performance and Systemic Biocompatibility. Issue 8 (10th November 2016) - Richtrova, Pavlina; Mares, Jan; Kielberger, Lukas; Trefil, Ladislav; Eiselt, Jaromir; Reischig, Tomas
Abstract: Reportedly, citrate‐based dialysis solution enables heparin dose tapering or even complete exclusion, particularly in postdilution hemodiafiltration (HDF). The aim of the study was to verify this strategy in predilution setting and to assess its short‐term safety, efficacy, and biocompatibility. Ten regular hemodialysis patients were assigned to predilution HDF on acetate‐ and citrate‐based dialysis solutions (0.8 mmol/l trisodium citrate) at random order. Acetate HDF was performed using routine dose of heparin while citrate HDF was heparin free. Plasma calcium, thrombin‐antithrombin complexes (TAT), and citrate levels were measured at 0, 30, 60, 120, and 240 min. Following each session, a semiquantitative dialyzer clotting score (DCT 1‐5) was assessed and HDF adequacy was determined as spKt/V. Statistical relevance was tested by ANOVA with p P < 0.05 held significant, data are given as means ± standard deviations. All sessions were accomplished successfully, premature termination or circuit re‐setting was not necessary. However, DCT was significantly higher in citrate‐HDF compared to acetate‐HDF regimen (3.4 ± 0.65 and 1.8 ± 0.79, respectively, P = 0.002) as well as TAT generation rate (increase per session by factor 11.0 ± 8.43 and 2.1 ± 1.26, respectively, P = 0.004 between regimens). Ionized calcium declined only by the end of citrate‐HDF (from 1.09 ± 0.086 to 0.99 ± 0.030 mmol/L, P = 0.002) yet without accompanying clinical symptoms. Systemic citrate levels increased along the citrate‐HDF session but stayed an order of magnitude below concentrations needed to establish citrate anticoagulation (peak at 0.276 ± 0.112 mmol/L). Dialysis adequacy estimated by spKt/V was found lower in citrate‐HDF vs. acetate‐HDF (1.48 ± 0.163 and 1.58 ± 0.165, respectively, P = 0.006). Although predilution HDF using citrate‐based dialysate is feasible without heparin, both dialysis adequacy and biocompatibility is significantly compromised. Therefore, this approach can be adopted for a single procedure but is not acceptable on a regular basis.